Di era digital saat ini, smartphone telah menjadi bagian tak terpisahkan dari masyarakat modern, dengan iPhone dari Apple menonjol sebagai produk premium yang menarik minat konsumen secara signifikan di Indonesia. Platform media sosial seperti YouTube dan - Aghniya Agustina; Deri Apriadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2025)
In today's digital era, smartphones have become an integral part of modern society, with Apple's iPhone standing out as a premium product capturing significant consumer interest in Indonesia. Social media platforms such as YouTube and Facebook play a vital role in shaping purchase decisions through reviews, recommendations, and promotional content. This study aims to compare the influence of YouTube and Facebook on iPhone purchasing decisions among consumers in Bandung City. Using a quantitative approach, data were collected via questionnaires and analyzed using SPSS. The results show that YouTube has a positive and significant influence on purchasing decisions, with a t-value of 2.584 > t-table 2.012 and a significance value of 0.013 < 0.05, meaning H1 is accepted. In contrast, Facebook does not have a significant influence, with a t-value of 0.984 < t-table 2.012 and a significance value of 0.611 > 0.05, meaning H2 is rejected. These findings provide strategic insights for Micro, Small Medium Enterprise (MSMEs) to prioritize platforms like YouTube in digital marketing planning especially when promoting technology or premium products like the iPhone